(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In order to determine the prevalence of refractive errors and the pattern of ocular morbidityamong the school children of a rural village, the purpose of this study was to gather this information. Across-sectional study was conducted on children aged 4 to 15 years old in a rural village -Damurdarpur,Jalandhar( Punjab). The location of the study was in India. Every child was given a full eye exam, whichconsisted of retinoscopy, refraction under cycloplegia, and a measurement of the child’s visual acuityusing Snellen’s E chart. In addition to that, the anterior segment, the media, and the fundii were allexamined. Myopia was defined as a sphericalcylindrical equivalent refractive error of at least -0.50 D,and hypermetropia was defined as having a refractive error of +0.50 D or more . The survey involved theexamination of 220 eyes belonging to 110 children, the majority of whom were in the age range of 5 to 10years old. There were 85.40 percent of people who had a prevalence of uncorrected visual acuity of 66.